The dynamic of leaf growth of harumanis mango grown in the control environment system with respect to time and energy domain - Najihah Binti Abd Jabbar (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
This project explained the growth of Harumanis mango leaves during wet and dry season. The objective of this research is to determine the growing degree day for leaf of Harumanis mango, measure length and width of leaf and evaluate energy for the leaf to grow by considering growing degree day value. The developmental growth of the leaves were observed from bud formation until the leaves reached maturity. In this project, growing degree day formula will be used to measure heat accumulation to predict the day for development of leaf. The values of daily growing degree day are added together from the beginning of the season. Growing degree day is very useful for estimating the growth development of leaf until the leaf reaches maturity. The growing degree day has been calculated each day until the leaves reached maturity. Base temperature used in this project was 28.5 0C. For this project the developmental growth of Harumanis mango leaves were bigger during wet season. While, during dry season the time for the leaves reached maturity were longer compared to wet season. The growing degree day of Harumanis mango leaf for both season was 91.25 0C. Length of the leaves was the best parameter to indicate the growth of Harumanis mango leaves.